2007
DOI: 10.1007/s10750-007-9029-x
|View full text |Cite
|
Sign up to set email alerts
|

Global diversity of dragonflies (Odonata) in freshwater

Abstract: Larvae of almost all of the 5,680 species of the insect order Odonata (dragonflies and damselflies) are dependent on freshwater habitats. Both larvae and adults are predators. The order is relatively well studied, and the actual number of species may be close to 7,000. Many species have small distributional ranges, and are habitat specialists, including inhabitants of alpine mountain bogs, seepage areas in tropical rain forests, and waterfalls. They are often successfully used as indicators for environmental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
84
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(99 citation statements)
references
References 20 publications
11
84
0
4
Order By: Relevance
“…Many are strong fliers, and most of them prefer open and half-shaded area. According to Kalkman et al (2008), open landscapes are generally better for tropical species to colonise new habitats and these dragonflies seem to be less influenced by habitat modification. They can recolonise impacted areas in the presence of good growth of riparian vegetations.…”
Section: Discussionmentioning
confidence: 99%
“…Many are strong fliers, and most of them prefer open and half-shaded area. According to Kalkman et al (2008), open landscapes are generally better for tropical species to colonise new habitats and these dragonflies seem to be less influenced by habitat modification. They can recolonise impacted areas in the presence of good growth of riparian vegetations.…”
Section: Discussionmentioning
confidence: 99%
“…one-third (9) of the families recorded for the entire Neotropics (21, Kalkman et al 2008) was found in the middle course of the Jacuí River. However, the pattern of their diversity in the Neotropical region (Kalkman et al 2008) was maintained.…”
Section: Discussionmentioning
confidence: 99%
“…one-third (9) of the families recorded for the entire Neotropics (21, Kalkman et al 2008) was found in the middle course of the Jacuí River. However, the pattern of their diversity in the Neotropical region (Kalkman et al 2008) was maintained. Libellulidae was represented by the most genera, followed by Coenagrionidae and Gomphidae, whereas Calopterygidae, Corduliidae, and Lestidae were represented by only one genus each.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations